PENERAPAN PROMOSI SOSIAL MEDIA SEBAGAI STRATEGI PEMASARAN UMKM (Journal Edutama Multidisciplinary Indonesian, 2025)
The Community Service Partners in this activity are Micro, Small and Medium Enterprises (MSMEs) engaged in the food sector, namely catering. The MSMEs that are the Community Service Partners have been established in Bogor City for a very long time, which is almost more than 10 years. However, their marketing activities are still very minimal and conventional. For this reason, these MSMEs need to be given training on the importance of utilizing digital marketing so that their marketing system becomes better so that they can expand the scope of their business targets and can support better sales activities. In addition, MSMEs are also given assistance in creating business accounts on social media, namely Facebook and Instagram, along with how to manage these digital media optimally. The outputs produced from this community service are Facebook and Instagram accounts, scientific articles published in national journals, and activity reports. The method used is to provide training in the form of lectures and tutorials on creating accounts on social media along with how to manage these digital media. From the results obtained in this activity, it is recommended that the use of digital marketing strategies can be followed up with periodic guidance so that they can be effective and optimal in supporting marketing activities and increasing sales of MSME businesses.